2019
DOI: 10.3390/ijms20133273
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Sleep Deprivation-Related Changes in N-methyl-D-aspartate Receptor—Nitric Oxide Signalling in the Rat Cerebral Cortex with Reference to Aging and Brain Lateralization

Abstract: Aging and chronic sleep deprivation (SD) are well-recognized risk factors for Alzheimer’s disease (AD), with N-methyl-D-aspartate receptor (NMDA) and downstream nitric oxide (NO) signalling implicated in the process. Herein, we investigate the impact of the age- and acute or chronic SD-dependent changes on the expression of NMDA receptor subunits (NR1, NR2A, and NR2B) and on the activities of NO synthase (NOS) isoforms in the cortex of Wistar rats, with reference to cerebral lateralization. In young adult cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 52 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…It was shown that ageing decreases expression of NMDA receptors and downregulates NOS isoforms in some SD groups. This also corroborates with cognitive decline in the elderly (Kristofikova et al 2019). SD activates oxidoinflammation in the prefrontal cortex, decreasing glutamate receptor subunits and PSD95 in PND33 (postnatal day 33) in rats.…”
Section: Glutamatergic Systemsupporting
confidence: 76%
“…It was shown that ageing decreases expression of NMDA receptors and downregulates NOS isoforms in some SD groups. This also corroborates with cognitive decline in the elderly (Kristofikova et al 2019). SD activates oxidoinflammation in the prefrontal cortex, decreasing glutamate receptor subunits and PSD95 in PND33 (postnatal day 33) in rats.…”
Section: Glutamatergic Systemsupporting
confidence: 76%
“…Chronic SD led to eNOS dysfunction and NR2A increased activity, while the acute SD elevated iNOS in the right side of rats' brains. Chronic SD and age both affected the NMDA prevalence and NOS functions in a similar manner in which AD does [246].…”
Section: Sleep Problems Aging and Nomentioning
confidence: 75%
“…Moreover, SD has been suggested to affect NMDA receptors which are involved in sleepwake cycles [244,245]. Kristofikova et al (2019) found that the expression of subunits of NMDA receptors (NR1, NR2A, and NR2B) and eNOS, as well as nNOS, were reduced in aged rats. Changes to the nNOS were correlated with NR1 and NR2B in both hemispheres of animals.…”
Section: Sleep Problems Aging and Nomentioning
confidence: 99%
“…This study found that rTMS can reverse the reduction of PSD-95 and SYP levels in the hippocampus of 3xTg-AD mice. Autopsy studies also found that the mRNA and protein expression levels of the postsynaptic glutamate receptors NR1, NR2A, and NR2B subunits decreased in AD patients [ 50 ]. In this study, it was found that the expression levels of NR1, NR2A and NR2B subunit proteins were down-regulated in the brain of 3xTg-AD mice, while rTMS only increased the level of NR2B, suggesting that rTMS may regulate glutamatergic transmission mainly by regulating NR2B.…”
Section: Discussionmentioning
confidence: 99%